Cognitive Behavior Therapy (CBT) sebagai Terapi Tingkat Kecemasan pada Lansia - Violeta Yuman Tanaya; Wachidah Yuniartika (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2023)
This study aims to determine the effect of Cognitive Behavior Therapy (CBT) on anxiety levels in older people in Gumpang Village. This study used the pre-experimental method with the type of pre-post test research in one group (one-group pre-post test design). The results of the Wilcoxon Rank Test showed that the mean value before Cognitive Behavior Therapy (CBT) was 18.61. In contrast, the Wilcoxon signed ranks test showed hostile ranks or the difference in anxiety scores for older people in Gumpang Village was 87, meaning 87 elderly experienced decreased anxiety scores after Cognitive Behavior Therapy. In contrast, the mean rank or average decrease in anxiety is 44.00. Statistical test with the Wilcoxon Asymp sig test. (2-tailed) is 0.000 (p < 0.05). In conclusion, there is an effect of Cognitive Behavior Therapy on the level of anxiety in older people in Gumpang Village, to be precise at the Ngudi Waras Posyandu and the Panca Marga 4 Posyandu, Kartasura District, Sukoharjo Regency, Central Java Province. Keywords: Cognitive Behavior Therapy, Anxiety, Elderly